Ephesians - Schüssler Fiorenza, Elisabeth, 1938- (Book collections on Project MUSE., 2017)
"Ephesians is a "mystery" text that seeks to make known the multifarious Wisdom of G*d. At its heart is the question of power. In this commentary, Elisabeth Schüssler Fiorenza examines the political understandings of ekklesia and household in Ephesians as well as the roles that such understandings have played in the formation of early Christian communities and that still shape such communities today. By paying close attention to the function of androcentric biblical language within Ephesians, Schüssler Fiorenza engages in a critical feminist emancipatory approach to biblical interpretation that calls for conscientization and change, that is, for the sake of wo/men's salvation or wellbeing."